Coke/Fe3O4 nanoparticle composites: synthesis, characterization and adsorption behaviour towards organic dyes. Issue 37 (8th August 2016) - Giri, S.K.; Sahoo, P.; Das, R.; Das, N.
Abstract: Coke/Fe3 O4 composites using varying sizes of coke samples derived from hard/soft coking coals blending with Fe3 O4 nanoparticles, generated in situ or added ex situ, were prepared and characterized by several physicochemical methods. Powder X-ray diffraction, UV–vis–DRS and SEM–EDX confirmed the presence of both coke and magnetite nanoparticles (MNP) in the composite samples, while transmission electron microscopy revealed nearly a uniform distribution of MNP on coke. The obtained composites combined the features of coke and Fe3 O4 nanoparticles were efficient and fast in the removal of several aqueous organic dyes and the adsorption efficiency was mainly depended on the solution pH, initial dye concentration and adsorbate/adsorbent ratio. Batch equilibrium adsorption results of congo red (CR) and methylene blue (MB) were best described by the Freundlich isotherm model. In comparison, the desorption of adsorbed dyes on composites was much easier in the case of anionic dyes like CR than cationic one (MB). The present study showed that the as-prepared coke/Fe3 O4 composites could be utilized as a low-cost efficient and magnetically separable adsorbent for the environmental remediation.